Performance checklist and its influence on knowledge and satisfaction of intensive care nurses: A quasi‐experimental study. Issue 3 (9th November 2022) - Imanipour, Masoomeh; Shahsavari, Hooman; Hazaryan, Mahsa; Mirzaeipour, Farshid
Abstract: Aim: The purpose of this study was to evaluate the impact of using a performance checklist on knowledge and satisfaction of intensive care nurses. Method: This study was a quasi‐experimental study and performed on 70 intensive care nurses in two groups. Performance checklists had to be filled by the nurses in experiment group during central venous pressure (CVP) measurement procedure. Knowledge and the nurses about standards of CVP measurement and their satisfaction were evaluated in both groups by a researcher‐made questionnaire. The data were analysed using the SPSS software. Results: In the experiment group, the level of knowledge significantly increased after the intervention ( p  = .001) and the majority of nurses (85.7%) had a high level of satisfaction. Also, there was a significant difference between mean knowledge scores of the two groups after the intervention ( p  = .006). Conclusion: This showed that applying performance checklists can influence nurses' knowledge and should consider a simple indirect educational method.